Using DCOP to Model Resource Allocation: A Review of Algorithms - Gularte, Alexander R.; Adamatti, Diana Francisca (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2013: Anais do VII Workshop-Escola de Sistemas de Agentes, seus Ambientes e AplicaçõesDO - 10.5753/wesaac.2013.33199, 2013)
Distributed Constraint Optimization Problem (DCOP) is a formalism that is widely used for coordination in multiagent systems. The advantage of applying these algorithms for multiagent coordination is due to the fact that them are distributed, robust and scalable. The aim of this work is to present a revision of the complete and incomplete algorithms, generally found in the literature and how these approaches can benefit the resource allocation in Multiagent Systems.